Effect of Implementing Guided Music Management Strategies on the Psychological State of College Students of Science and Technology During Their Graduation Reply - Jin Li (Noise and Health)
Purpose: To study the effect of guided music management strategies on the psychological state of college students of science and technology during their graduation reply. Methods: A retrospective analysis was conducted on the relevant data of 107 college students of science and technology who underwent graduation defense in 2022. These students returned to school 1 week before their graduation reply. On the basis of whether they received guided music management strategies, the students were divided into a control group (no management strategy) and an observation group (received guided music management strategies). Among the students, 50 were included in the observation group after excluding two who did not meet the inclusion criteria. A total of 53 students were included in the control group after excluding 2 who did not meet the inclusion criteria. General demographic information and Self-Rating Anxiety Scale (SAS), Test Anxiety Scale (TAS) and Chinese Perceived Stress Scale (CPSS) scores were collected. Results: No significant differences in SAS, TAS and CPSS scores were found between the two groups before management (P > 0.05). After management, the SAS score of the observation group was lower than that of the control group (P < 0.05). The TAS and CPSS scores of the observation group after management were lower than those of the control group (P < 0.05). Conclusion: Implementing guided music management strategies can effectively alleviate anxiety and stress in college students of science and technology during their graduation reply and has a certain utility and promotion value.